Batch Single-Stage Co-Digestion of Olive Mill Wastewater with Cattle Manure: Modeling, Simulation, and Validation - Ismaili, Samir; Zrelli, Adel; Elfalleh, Walid; Ghorbal, Achraf (Engineering, Technology & Applied Science Research, 2024)
The co-digestion of agri-food by-products, such as Olive Mill Waste (OMW) and Cattle Manure (CM), is an efficient method for waste management and biogas production. OMW, characterized by a high soluble organic content, low methane yield, and limited biodegradability, contrasts with the easily degradable properties of CM. The synergistic use of these wastes enhances the hydrolytic-acidogenic phase, increasing the availability of Volatile Fatty Acids (VFAs) and thereby boosting biogas production through bacterial fermentation of VFAs. This study introduces a novel mathematical model for mesophilic anaerobic co-digestion of OMW and CM in batch reactors. The uniqueness of the model lies in its ability to balance comprehensiveness with simplicity, implemented in MATLAB, for both precision and user-friendliness. Its focus on crucial factors, such as total VFA and methane generation, sets it apart in the field of anaerobic digestion modeling. The exceptional performance of the model is evidenced by its high accuracy in predicting experimental results, achieving impressive R² values of 0.96469 and 0.99133 for 50:50 and 75:25 OMW to CM ratios, respectively. These results demonstrated the robustness of the model in simulating key co-digestion parameters across varying substrate compositions. By enhancing the feasibility of numerical computation while maintaining high predictive accuracy, this approach represents a significant advance in biogas production optimization. The practical applicability and accuracy of the model make it a valuable tool for optimizing real-world waste management and renewable energy production processes, potentially leading to improved methane yields and overall biogas production.